Identifying the Prophetic Legal Ethos in the Death Penalty Provisions of the Indonesian Criminal Code - Daeng Robo, Basto (Fiat Justisia: Jurnal Ilmu Hukum, 2024)
Amid the ongoing controversy surrounding the drafting process of the Indonesian Criminal Code, particularly with respect to the provisions on the death penalty, this study seeks to explore the ethos or spirit of prophetic law through a philosophical examination of these regulations. This research employs a normative legal methodology, utilizing both statutory and conceptual approaches. The concepts of humanization, liberation, and transcendence serve as foundational elements of the philosophical framework of prophetic law, which coherently and sequentially aligns with the structures of ontology, epistemology, and axiology. These concepts are employed as benchmarks to identify the prophetic legal ethos embedded within the death penalty provisions of the Indonesian Criminal Code. Essentially, the arrangements pertaining to the death penalty are positioned as instruments for societal education. If a convict sentenced to death demonstrates genuine remorse and makes efforts toward rehabilitation, the imposition of the death penalty may be reconsidered in favor of life imprisonment. This perspective aligns with the principles articulated in QS. Al Maidah (5:38–39), which emphasize that punishment is intended for self-improvement. Should the convict exhibit remorse prior to execution, it reflects the understanding that Allah is the Most Forgiving. This approach underscores a legal philosophy that prioritizes the substantive and soulful dimensions of law, rooted in the prophetic legal ethos of humanization, liberation, and transcendence.